Exploration of Nurse Knowledge with Splints on Fracture Patients in Hospitals - Prestasianita Putri; Alfid Tri Afandi; Yunus Saifur Rizal (D'Nursing and Health Journal (DNHJ), 2022)
Intoduction: One of the main tasks of nurses in providing nursing care is placing splints on patients with fractures. This installation mechanism and procedure requires more knowledge and experience so it is hoped that there will be no mistakes. This study aims to identify knowledge related to splinting in patients with fractures. Method: Non-experimental with a descriptive research approach with the aim of describing each variable. The population of this study was nurses who worked in the surgical inpatient room using a total sampling technique. The number of respondents in this study was 51 people. Data collection techniques using a questionnaire. Result: Respondent data showed that the majority of respondents were male (62.7%), aged 26-45 years (100%), D3 Nursing education (62.7%), worked more than 3 years (100%), position in the room the majority of nurses were implementing (80.4%).  The results of this study were that most of the nurses' knowledge was good (80.4%), the majority of the splints were good (72.5%). Conclusion: The characteristics of nurses can affect the results of the knowledge of nurses who will be evaluated. Therefore, experience, education, and position can also be a benchmark in knowing a nurse's competence. Nurses need to increase competence in their respective fields so that they can improve the quality of service.